MOD E LING EXPLOSIVE ORDNANCE SEARCH AND DETECTION PROCEDURES BY RADAR TECHNIQUES - Volodymyr I. Kotsiuruba (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
Base d on the analysis of existing approaches to the m odeling of demining, namely, use of electroma gnetic method s of prospecting and detecting man-made objects in harboring environments (soil, snow, water, etc.), was proposed an improved mathematical model of search and detection of explosives by a radar method, which, unlike existing ones, takes into account: the parameters of the zone of the guaranteed exposure to explosive hazards (the concept was introduced for the first time) at specified depths of their installation in covering environments, the characteristics of the directivity of the electromagnetic field in the justification of requirements to the means of searching on the movable base, and the dependence of the necessary angle of the antenna from the maximum distance of detection of explosive objects by the radar method. Besides, it was found the dependence between the width of the main beam of the directivity diagram at the level of 0.5 from its maximum power settings and the parameters of the zone of guaranteed detection of the explosive devices. The suggested improvements of the mathematical model and the sequence of calculations will increase the accuracy of simulation results of the process of search and detection of explosive devices in environments harboring in the justification of requirements for clearance of this type.